2010
DOI: 10.1111/j.1365-2664.2010.01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of stream macroinvertebrates and ecosystem function to conventional, integrated and organic farming

Abstract: Summary1. Organic farming practices can benefit a wide range of terrestrial biota in comparison to conventional farming but we do not know whether this benefit extends to streams flowing through farmed landscapes. 2. We measured the impacts of organic, integrated management and conventional farming on the taxonomic and trait composition of macroinvertebrate communities and on stream ecosystem functioning (algal accrual on tiles and leaf breakdown). Our study design included five replicates of each farming prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 35 publications
9
36
0
Order By: Relevance
“…This exchange of resources can subsidise different trophic levels (Marczak et al 2007), alter species interactions and community composition in both systems (Baxter et al 2005;Marcarelli et al 2011;Nakano and Murakami 2001) and influence food web stability (Huxel and McCann 1998). As a consequence, changes within one ecosystem are likely to affect the structure and function of adjacent ecosystems.…”
Section: Introductionmentioning
confidence: 98%
“…This exchange of resources can subsidise different trophic levels (Marczak et al 2007), alter species interactions and community composition in both systems (Baxter et al 2005;Marcarelli et al 2011;Nakano and Murakami 2001) and influence food web stability (Huxel and McCann 1998). As a consequence, changes within one ecosystem are likely to affect the structure and function of adjacent ecosystems.…”
Section: Introductionmentioning
confidence: 98%
“…Outcomes from these IM growers are sometimes quite different from so-called "conventional' farmers. For example, in the ARGOS project, macoinvertebrate communities and ecosystem functioning were negatively impacted in streams running through conventional sheep/beef farms, but there was no evidence of them being different in Organic and IM farms (Magbanua et al, 2010).…”
Section: What Should Organic Farming Be Compared Against?mentioning
confidence: 99%
“…Jarvie [10] highlighted the small relative contribution of PP derived from agriculture to water eutrophication in lowland rivers in comparison with sewage effluent sources. Therefore SRP desorption from sediment particles represents an ecological risk in individual reaches of rivers where SRP concentrations are low at times of eutrophication risk [4,10,75].…”
Section: Transport Managementmentioning
confidence: 99%
“…Several published studies have demonstrated the impact of diffuse agricultural pollution on rivers ecological functions as a result of poor water quality [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%